The influence of local criotherapy on hand swelling and pain reduction in patients diagnosed with rheumatoid joint inflammation - Pop, Teresa; Kwolek, Andrzej; Szuberla, Marta (European Journal of Clinical and Experimental Medicine, 2009)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Rheumatoid joint inflammation is lingering, auto immunologically based disease with acute and remission periods. The disease is more frequent in case of women of various ages. The death rate in the patients, compared with general population, is two times higher. The purpose of the paper is to evaluate the influence of local criohterapy on hand swelling and pain reduction in patients diagnosed with rheumatoid joint inflammation. The researched group consisted of 33 patients, aged 31-78, diagnosed with rheumatoid joint inflam‘mation. In all cases the criotherapy treatment was applied. The treatment lasted for 3 minutes and was performed once a day, before exercises. The exercises were performed on 618 of patients. In case of 39% of patients the exercises did not include the hand joints. All patients underwent the measurements at the wrist level, the width of hand and pain evaluation which were conducted according to VAS pain scale. The effective efficiency was evaluated according to 4-grade Gofton scale. The research has proven beneficial influence of criotherapy on decrease of hand swelling and pain of joints. Better results were acquired in case of patients who underwent exercises after criotherapy treatment.